User-centered design of a web application for an online Operating Systems course - José Daniel Calvo Saiz; Sonia Pamplona Roche (Centro de Estudios Financieros, 2017)
Operating Systems is a course included in the curricula of Computer Science Engineering that is difficult to teach and learn. This difficulty may be greater in online environments, where synchronous teacher-student contact may be very rare. This paper presents a web application whose purpose is to facilitate the learning of the subject Operating Systems in online environments. This application allows the study of concepts related to the management of operating systems processes and to check their understanding. In order to increase the usability, usercentered design techniques have been used to create the application.